ANALISIS DAN PERENCANAAN BALOK BETON BERTULANG DENGAN SISTEM PRECAST IN SITE - I Made Letra; I Gede Gegiranang Wiryadi; I Gede Oka Darmayasa; Ni Wayan Yuni Astari (Jurnal Ilmiah Kurva Teknik, 2021)
Reinforced concrete beams in this study are designed precast in site or cast before being installed in position. This beam is made only by casting the beam reduced by the thickness of the plate and without the top reinforcement, while the lower reinforcement and shear reinforcement is still installed as required from the analysis. The goal is to shorten the working time and get better concrete quality. This beam is part of the structural elements of a building that has been designed and analyzed in advance with a computer program based on structural analysis, SAP2000 v.16. Dimensions and reinforcement requirements from the results of the structural analysis are used as references to analyze precast in site beams. Main beam dimensions resulting from building structure analysis are B1, B2, and B3 with dimensions of 300x500 mm, but with different amounts of reinforcement requirements. Meanwhile, the joist (BA) has dimensions of 250x400 mm. Then the precast in site beams B1, B2, and B3 have dimensions of 300x350 mm and joists (BA) have dimensions of 250x250 mm after deducting the plate thickness of 150 mm. After being cast and dried at the planned age, the beam is then lifted and positioned on the column provided, after which the upper reinforcement and slab reinforcement are installed and cast again. Analysis of lifting or erection is also carried out to ensure that the working load does not exceed its capacity. The analysis results show that the precast beam is able to carry all the working loads and the precast in site system can be applied safely.